1987
DOI: 10.1111/j.1365-2265.1987.tb00797.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Diagnostic Criteria for Leydig Cell Tumours in Adult Men Revealed by Gynaecomastia

Abstract: Gynaecomastia caused by Leydig cell tumours (LCT) in adult men may appear a long time before clinical evidence of testicular swelling. To evaluate the diagnostic criteria for LCT, hormonal status was studied in 14 cases and compared with results of a control group (CG) and 10 men with idiopathic gynaecomastia (IG). The mean plasma T level was significantly (P less than 0.005) lower in LCT (16.7 +/- 1.7 SEM nmol/l) than in CG (23.0 +/- 1.3 nmol/l). However, individual plasma T levels were in the normal range in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
19
0
2

Year Published

1997
1997
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 22 publications
6
19
0
2
Order By: Relevance
“…Leydig cell tumors and rare adrenal feminizing tumors) are associated with a typical hormonal pattern, including 1) increased plasma levels of estrogens [17␤-E2 and/or estrone (E1)], 2) low plasma gonadotropin levels, and 3) a more or less marked reduction in plasma T levels (1)(2)(3)(4). These hormonal patterns reflect the E2-induced inhibition of gonadotropin secretion, as previously shown under physiological (5) and pathological conditions (6).…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Leydig cell tumors and rare adrenal feminizing tumors) are associated with a typical hormonal pattern, including 1) increased plasma levels of estrogens [17␤-E2 and/or estrone (E1)], 2) low plasma gonadotropin levels, and 3) a more or less marked reduction in plasma T levels (1)(2)(3)(4). These hormonal patterns reflect the E2-induced inhibition of gonadotropin secretion, as previously shown under physiological (5) and pathological conditions (6).…”
mentioning
confidence: 82%
“…This mechanism has been observed in feminizing adrenal tumors (2) and has been recently demonstrated to be physiologically present in normal men (7). However, in feminizing tumors, FSH appeared more frequently and more strongly suppressed than LH (3,6), suggesting that tumor secretion could also directly inhibit pituitary FSH synthesis and/or secretion. In agreement with this hypothesis, it has been shown that E2, in addition to its hypothalamic action, is able to reduce FSH secretion through a direct effect on gonadotrophs (4,8).…”
mentioning
confidence: 89%
“…In normal adult men, plasma E 2 and T levels reach a peak 24 and 72 h respectively after a single i.m. injection of a pharmacological dose (1500-5000 IU) of ehCG (12,14,15,(17)(18)(19)22). The stimulating effect of ehCG, mediated through the activation of the LH/hCG receptor of the Leydig cell, involves the amplification of the enzymatic pathways of sex steroid synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The stimulating effect of ehCG, mediated through the activation of the LH/hCG receptor of the Leydig cell, involves the amplification of the enzymatic pathways of sex steroid synthesis. Furthermore, a gonadotropininduced activation of Leydig cell aromatase leads to a rise in E 2 synthesis (14,17,23). Multiple injections of ehCG give similar results as a single one (16,24,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation